The Economic Effects of International Sanctions: An Event Study - Jerg Gutmann; Matthias Neuenkirch; Florian Neumeier (University of Hamburg, Institute of Law and Economics (ILE), 2021)
Although international sanctions are a widely used instrument of coercion, their economic effects are still not fully understood. This study uses a novel dataset and an event study approach to evaluate the economic consequences of international sanctions, thereby accounting for pre-treatment dynamics in countries subject to sanctions. Our analysis focuses on the effects of sanctions on GDP growths as well as various transmission channels through which sanctions affect economic activity. We document a significant negative effect of international sanctions on GDP growth and its components (consumption, investment, and government expenditures) as well as on trade and foreign direct investment. Additional panel difference-in-differences estimations reveal that this detrimental effect is driven by financial sanctions and US unilateral sanctions.
Keywords: F43; F51; F52; F53; O43; O47; 330; economic growth; event study; international sanctions; transmission channels